Bond returns and market expectations - Carlo Altavilla; Raffaella Giacomini; Riccardo Costantini (Centre for Microdata Methods and Practice (cemmap), 2013)
A well-documented empirical result is that market expectations extracted from futures contracts on the federal funds rate are among the best predictors for the future course of monetary policy. We show how this information can be exploited to produce accurate forecasts of bond excess returns and to construct profitable investment strategies in bond markets. We use a tilting method for incorporating market expectations into forecasts from a standard term-structure model and then derive the implied forecasts for bond excess returns. We find that the method delivers substantial improvements in out-of-sample accuracy relative to a number of benchmarks. The accuracy improvements are both statistically and economically significant and robust across a number of maturities and forecast horizons. The method would have allowed an investor to obtain positive cumulative excess returns from simple riding the yield curve investment strategies over the past ten years, and in this respect it would have outperformed its competitors even after accounting for a risk-return tradeoff.
Keywords: G1; E4; C5; 330; Yield curve modelling; Futures; Market Timing; Exponential tilting; Kullback-Leibler